Sensitivity of Larva Spodoptera litura Against the Density of Spores of Fungi Metarhizium anisopliae on the Onion Plant Red (Allium cepa) in the Laboratory - Brijayanti Halawa; Azwana Azwana; Ellen L. Panggabean (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Sensitivity of Larva Spodoptera litura Against the Density of Spores of Metarhizium anisopliae Fungi On the Red Onion Plant ", aims to determine the density of Metarhizium anisopliae spores which are effective in controlling the spodoptera litura pests that attack onion plants. This research was conducted by using Randomized Complete Random (RAL) Factorial ie instar larvae and spore density. The parameters observed were behavioral and morphological changes as well as percentage mortality of Spodoptera litura larvae. The results showed that: Changes in behavior and morphology of insects in the form of slow movement, decreased appetite and larval body surface covered by the fungus is light green and dark green. The density of spores of M. anisopliae to S. litura pest has a very significant effect on the percentage of S. litura mortality since the age of 1-9 HSA. The percentage of S. litura mortality tended to increase with higher spore density of M. anisopliae and instar 1-3 being more sensitive instar than instar 4-6 Spodoptera litura larvae. Mortality of S. litura is most prevalent in I1M3 treatment (instar 1-3 with spore density 106).